Trained Immunity: An Overview and the Impact on COVID-19 - Brueggeman, Justin M.; Zhao, Juan; Schank, Madison; Yao, Zhi Q.; Moorman, Jonathan P. (Frontiers in Immunology, 2022)
Effectively treating infectious diseases often requires a multi-step approach to target different components involved in disease pathogenesis. Similarly, the COVID-19 pandemic has become a global health crisis that requires a comprehensive understanding of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) infection to develop effective therapeutics. One potential strategy to instill greater immune protection against COVID-19 is boosting the innate immune system. This boosting, termed trained immunity, employs immune system modulators to train innate immune cells to produce an enhanced, non-specific immune response upon reactivation following exposure to pathogens, a process that has been studied in the context of in vitro and in vivo clinical studies prior to the COVID-19 pandemic. Evaluation of the underlying pathways that are essential to inducing protective trained immunity will provide insight into identifying potential therapeutic targets that may alleviate the COVID-19 crisis. Here we review multiple immune training agents, including Bacillus Calmette-Guérin (BCG), β-glucan, and lipopolysaccharide (LPS), and the two most popular cell types involved in trained immunity, monocytes and natural killer (NK) cells, and compare the signaling pathways involved in innate immunity. Additionally, we discuss COVID-19 trained immunity clinical trials, emphasizing the potential of trained immunity to fight SARS-CoV-2 infection. Understanding the mechanisms by which training agents activate innate immune cells to reprogram immune responses may prove beneficial in developing preventive and therapeutic targets against COVID-19.